The Development of the Concept of Copyright in Islamic Civilization: A Historical and Contemporary Study - Muhammad Zaenal Arifin; Khusnudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Before the First Industrial Revolution, the concept of property in society was generally limited to physical objects with clear economic value. However, this revolution brought a significant paradigm shift, introducing copyright as a new form of property with legal protection. This study explores how Islam views copyright, using a historical-normative approach to demonstrate that the concept of property in Islam actually accommodates copyright as a valuable asset. Although the discourse on copyright in Islam has only developed in the contemporary era, the works of scholars such as Wahbah Zuhaili have provided a clear basis for the importance of protecting intellectual property. This research aims to dig deeper into the existence of copyright in the Islamic context, as well as how changes in social and economic values have influenced this understanding. Thus, this study offers important insights into the interaction between Islamic law and the development of copyright in the modern world.